Building a culture of conscious leadership - Potter, David; Starke, Jens (London ; New York : Routledge Taylor & Francis Group, 2023)
The key driver of disengagement amongst employees is a lack of psychological safety, generated from weak and underdeveloped intra and interpersonal skills on the part of managers. Addressing the issue head on, this book enables leaders to lead with conscious awareness to build and sustain psychologically safe cultures through which team members may positively engage with work in a far more meaningful and purposeful way. All too often leadership-follower relationships are purely transactional and focus on errors and problems resulting in an impoverished transactional leadership culture. These dynamics result in weak rapport, low levels of emotional intelligence on the part of line managers, and subsequently employee disengagement. This book unpacks these drivers in detail and builds a model that can be used as the basis of personal development and as a large-scale intervention into the leadership culture of an organization. This model is very accessible and can be used in a structured training programme through a series of action learning workshops based upon coaching relationships and mutual dialogue. The book is ideal reading for HRM managers, change leaders, learning and development managers, students of management and leadership, and line managers in organisations who are involved in leadership roles.
Includes bibliographical references and index.
Keywords: Leadership; Business